Mapping Civil Society Formation in Encouraging Issues of Public Accountability in Ngawi Regency, East Java - Khoyrul Anwar; Herviyanto Yusuf; Endang Setyaningsih Susilorini; Istiana Wijayanti Mala (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Efforts to mainstream the ideas and practices of public accountability are increasingly prominent, in line with the continued development of the practice of the principles of good governance. Since then and until now the issue of accountability remains the main stream discussed in the public space and strives to be practiced by all government institutions. In an effort to map the progress of Civil Society Organizations in Ngawi Regency in promoting accountability practices in the public sector, the purpose of this study is related to several things, namely: (1) to identify the strengths of Civil Society Organizations in Ngawi District; (2) identify the level of influence of Civil Society Organizations on accountability issues; (3) identify patterns of relation between Civil Society Organizations on issues of public sector accountability. This study method uses data collection techniques through interviews and focused group discussions (FGD). The results of this study found that: (1) Civil Society Organizations strength is still in a weak position, in general Civil Society Organizations activities are only driven by funding agencies, (2) the influence of Civil Society Organizations on accountability issues is influenced by their financial base and ability to build networks, including by becoming a local government partner, (3) the relationship pattern in interactions between Civil Society Organizations in Ngawi Regency is determined by two aspects, namely: psychological bond tied by the common ground and agenda of the issues being fought for, including issues of transparency and public sector accountability.